Pembangunan Aplikasi Dashboard Untuk Analisa Efektivitas Marketing Online Berbasis Website (Studi Kasus: Digital Marketing Malang) - Ubaidillah Hakim Fadly; Fajar Pradana; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Internet marketing is a form of marketing through internet media. Social Media Advertising (SMA) is one way of internet marketing who use social media. Facebook is one of social media can provide advertising or SMA, that have advantages with a large excess of users. Digital Marketing Malang (DMM) is a service company that offers paid advertising on Facebook. In practice, the DMM will experience difficulties when overseeing the number of many ads that are running, because when advertising a product, it requires a lot of splitting. Splitting is a strategy of breaking up ads with different compositions to get the most effective ads. For this reason, is necessary to build a dashboard application to analyze the effectiveness of online marketing that can automatically check ads every 1 hour in a set of ads that will stop advertising less effective. Application will be development with sequential waterfall model. The stages in this study are: literature studies, needs analysis, design, implementation, testing, conclusions and suggestions for future research. This application is built using a website base with the PHP programming language. Functional testing carried out in the form of unit testing, integration and validation that produces a 100% valid value. While the non-functional testing is done using compatibility testing with the results of the application can run well on 4 different browsers.